PARTISIPASI MASYARAKAT DALAM PENGELOLAAN ALOKASI DANA DESA DI DESA LEMOH TIMUR KECAMATAN TOMBARIRI TIMUR KABUPATEN MINAHASA - Lenak, Christin Novita; Rares, Joyce Jacinta; Tampi, Gustaf Budi (Sam Ratulangi University, 2015)
ABSTRACK : To realize the goal of national development, the government is giving great attention tothe development in the countryside. To the need to increase the participation of rural communities, as aform of cooperation between the government and the community in building a region (especially ruralareas). By utilizing the Village Fund Allocation (ADD), the village could play a more active in mobilizingcommunity development. The issue is still low community participation in village activities financed fromthe Village Fund Allocation. This was due to the lack of socialization and communication of governmentand society. The purpose of this study is to provide an overview of community participation in themanagement of the Village Fund Allocation (ADD) in the village of East Lemoh District of EastTombariri. This study used a qualitative approach, with a view to obtaining an overview of communityparticipation in the management of the Village Fund Allocation. Data collection techniques in this studyby observation, interviews, and documentation. The Results showed that public participation in themanagement of the Village Fund Allocation is still not optimal because the public just so much involved inimplementation, lack of awareness about existing Village Fund Allocation. Public awareness is stilllacking to participate also caused because of lack of socialization of the government on the allocation ofvillage funds. Thefore the suggestion of this research, rural government should always socialize theVillage Fund Allocation Policy (ADD) to the public so that the public could understand the policy.Keywords: Public Participation, Management, Village Fund Allocation.